Tioxolone niosomes exert antileishmanial effects on Leishmania tropica by promoting promastigote apoptosis and immunomodulation - Maryam Hakimi Parizi; Iraj Sharifi; Saeedeh Farajzadeh; Abbas Pardakhty; Mohammad Hossein Daie Parizi; Hamid Sharifi; Ali Reza Keyhani; Mahshid Mostafavi; Mehdi Bamorovat; Ahmad Khosravi; Daryoush Ghaffari (Asian Pacific Journal of Tropical Medicine, 2019)
Objective: To explore the antileishmanial effect of tioxolone and its niosomal form against Leishmania tropica. Methods: Tioxolone niosomes were prepared by the hydration method and were evaluated for morphology, size, release study, and encapsulation efficiency. The cytotoxicity of tioxolone and its niosomal form was measured by MTT assay, leishmanicidal activity against promastigote and amastigote by MTT assay, apoptosis by flow cytometry, IL-12, IL-10 and metacaspase gene expression levels by q-PCR. Results: Span/Tween 40 and Span/Tween 60 niosomes had good physical stability as depicted in their size distribution curves and high encapsulation efficiency (>99%). The release profile of the entrapped compounds showed Fickian’s model of tioxolone delivery based on diffusion through lipid bilayers. With the IC50 value for amastigote as (24.5±2.1) μg/mL and selectivity index as 10.5, the Span/Tween 60 niosome (NT2) had a superior effect to other drugs. The CC50 value and IC50 of promastigote value for NT2 were (257.5±24.5) μg/mL and (164.8±20.6) μg/ mL, respectively. The flow cytometric analysis showed that tioxolone and niosomal forms induced apoptosis of Leishmania tropica promastigotes in a dose-dependent manner. NT2 increased the expression level of IL-12 and metacaspase genes and decreased the expression level of the IL-10 gene. Conclusions: Niosomes of tioxolone play an immunomodulatory role in increasing Th1 cytokine profile and inhibiting the Th2 cytokine profile. It could be used for treatment of anthroponotic cutaneous leishmaniasis.